2019
DOI: 10.1021/acsnano.9b06772
|View full text |Cite
|
Sign up to set email alerts
|

Rotation-Selective Moiré Magnification of Structural Color Pattern Arrays

Abstract: When a microlens array is aligned and overlaid on an array of patterns with similar periodicity, a highly magnified image of the patterns is observed. This effect, known as moirémagnification, is used to reveal micropatterns that are unresolvable by the naked eye. These patterns are typically limited by print resolution to single color patterns. Here, we demonstrate the potential to selectively reveal more than one set of color patterns. By rotating a microlens array relative to a print containing three overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A Vero Clear 14 based SMP photoresist was developed (See Methods and Figure S1 for the preparation process). To test the resist, we placed a droplet of it onto a fused silica glass substrate and exposed using in the commercial TPL system Nanoscribe GmbH Photonic Professional GT using the "dip-in" configuration 40,52,53 . During exposure, photo-initiators at the focal point of the objective are activated by two-photon excitation from the femtosecond pulsed laser at 780 nm wavelength, leading to polymerization of the resist into solid structures.…”
Section: Two-photon Polymerization Lithography Of Shape Memory Polymermentioning
confidence: 99%
“…A Vero Clear 14 based SMP photoresist was developed (See Methods and Figure S1 for the preparation process). To test the resist, we placed a droplet of it onto a fused silica glass substrate and exposed using in the commercial TPL system Nanoscribe GmbH Photonic Professional GT using the "dip-in" configuration 40,52,53 . During exposure, photo-initiators at the focal point of the objective are activated by two-photon excitation from the femtosecond pulsed laser at 780 nm wavelength, leading to polymerization of the resist into solid structures.…”
Section: Two-photon Polymerization Lithography Of Shape Memory Polymermentioning
confidence: 99%
“…179 One potential application of structural colors is in decoration and consumer products. Due to the fade-resistant nature of structural colors, they can be used in unique and covert product tagging of luxury items, 12,192,193 e.g., with colorful miniature models, as shown in Figure 3a where colors are realized by shrinking three-dimensional (3D) photonic crystals. 78 Another interesting application is colorimetric sensing.…”
mentioning
confidence: 99%
“…Instead of a compound system, we designed our system (Fig. 1b ) with a hollow tower to support a spherical plano-convex microlens above a block of structural colour pixels that contains an array of nanopillars 8 , 30 , 31 . We refer to this system as a display unit.…”
Section: Resultsmentioning
confidence: 99%
“…2b ), we found that the focal plane shifted in the negative z-direction due to another aberration known as field curvature, which causes light rays with different field angles ( θ ≥ 0°) to focus on a curved surface rather than on a flat plane. Despite the presence of aberrations, the microlens behaves as intended: an optical router 31 that directs light rays from selected pixel positions to the observer. In the thin lens approximation, the pixel’s position selected by the microlens is expressed in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation